On Topological Indices of mth Chain Hex-Derived Network of Third Type - Huo, Yuhong; Ali, Haidar; Binyamin, Muhammad Ahsan; Asghar, Syed Sheraz; Babar, Usman; Liu, Jia-Bao (Frontiers in Physics, 2020)
In theoretical chemistry, the numerical parameters which are used to characterized the molecular topology of graphs are called topological indices. Several physical and chemical properties like boiling point, entropy, heat-formation and vaporization enthalpy of chemical compounds can determined through these topological indices. Graph theory has a considerable use in evaluating the relation for various topological indices of some derived graphs. In this paper, we will compute the topological indices like Randi´ c, first Zagreb, Harmonic, augmented Zagreb, atom-bond connectivity and geometric-arithmetic indices for Chain Hex derived network of type 3 CHDN3(m,n) for different cases of m and n. We will also compute the numerical computation and graphical view to justify our results.